Pengaruh Kemudahan Dan Harga Terhadap Keputusan Pembelian Pada E Commerce: Studi Kasus Pada Zalora Indonesia - Suryabhuana, Shalika Tertiera (CV. Green Publisher Indonesia, 2025)
This study aims to analyze the influence of convenience and price on consumer purchase decisions on the Zalora Indonesia e-commerce platform. Data were collected from 123 respondents through a questionnaire and analyzed using validity, reliability, normality, heteroscedasticity, multicollinearity, linear regression, t-test, F-test, and determination coefficient test. The results of the study show that convenience and price significantly influence consumers' purchasing decisions in Zalora. The resulting regression model was significant and was able to explain 67.6% of the variation in purchasing decisions. These findings imply that Zalora needs to continue to improve the platform's ease of use and implement a competitive pricing strategy to increase sales and strengthen its market position.